Patterns of Distribution of Phoretic Deutonymphs of Uropodina on Longhorn Beetles in Białowieża Primeval Forest, Central Europe - Szymon Konwerski; Jerzy M. Gutowski; Jerzy Błoszyk (Diversity, 2020)
We studied the distributional patterns of phoretic deutonymphs of the genera Oodinychus and Trichouropoda (Uropodina) on the longhorn beetles Monochamus sartor urussovii, Plagionotus detritus, Tetropium castaneum, and Te. fuscum, based on large samples of specimens (992 beetles and 25,587 mites) collected in the Białowieża Primeval Forest in Central Europe in the years 2008 and 2012–2016. All the studied phoretic phoront-host associations are characterized by different patterns of the attachment sites of mites on beetle’s body. In the case of O. ovalis and M. sartor urussovii association, the deutonymphs were found mostly on the pronotum and dorsal surface of the elytra. This is the only instance in which phoronts were absent on the legs. Deutonymphs of T. sociata on P. detritus preferred the abdomnen (both tergites and ventrites) and the hindlegs. Only in this case the phoronts were attached inside the subelytral space. The highest number of deutonymphs of T. shcherbakae on both Tetropium species occured on the legs. In the case of Te. castaneum, similar proportions of mites were recorded on all pairs of legs, while the preferred location of mites phoretic on Te. fuscum were the forelegs. Both the preferences of phoretic deutonymphs for specific parts of the host’s body and the participation of carriers transporting deutonymphs on particular parts of their bodies were very consistent.